An Epidemiological Study on Obesity and Its Determinants among Urban Slum Women of Rajkot City, Gujarat - Lunagariya, Ruchita T; Patel, Umed V (National Journal of Community Medicine, 2019)
Background: Every year at least 2.8 million adults die due to overweight or obesity. Most of the world's population lives in countries where overweight and obesity kills more people than underweight. In informal settlements like slums, NCDs are at particular risk of going undetected by formal health registries until presentation in a late stage of disease or death. NCDs among women have major health challenges. Objectives: To assess prevalence, determine factors responsible for Obesity. Methods: This is a cross sectional study conducted among 405 slum women of age 35 years or more in Rajkot city. Interview and anthropometric measurements like Height and weight were measured for all participants. Results: Total 93 (22.96%) women were diagnosed to be obese and 119 (29.38%) women were pre obese in present study. There was a statistically significant association between socio-economic classification (p=0.050), eating fat rich diet (p=0.004), walking (p=0.000), stress (p=0.033), parental history (p=0.000), sibling history (p=0.002) and obesity. Conclusions: Studied population has high prevalence of overweight and Obesity.